If you needed an organ transplant would you have one? The effect of reciprocity priming and mode of delivery on organ donor registration intentions and behaviour. Issue 3 (26th May 2017) - O'Carroll, Ronan E.; Haddow, Lorna; Foley, Laura; Quigley, Jody
Abstract : Objective: There are approximately 6, 500 people on the UK national transplant waiting list, around 400 of whom die every year. Only 35% of the UK population are currently on the organ donation register. We report two studies examining whether a reciprocity prime, in which participants were asked whether they would accept a donated organ, increased organ donation intentions and behaviour. Design: Between‐participants, randomized controlled design. Methods: In two studies, participants who were not currently registered organ donors took part either face‐to‐face or online and were randomly allocated to a reciprocity prime or control condition. Following the manipulation, they were asked to indicate, on either a paper or online questionnaire, their intention to join the organ donor register. Study 2 was similar to Study 1 but with the addition that after reporting intention, participants were then offered an organ donation information leaflet or the opportunity to click a link for further information (proxy behavioural measure). Results: In both studies, reciprocity primed participants reported greater intentions to register than controls. However, in Study 2, no effect on donation behaviour was found. Conclusions: Reciprocal altruism may be a useful tool in increasing intentions to join the organ donor register. Further evaluation is required to determine whether this increase in intention can be translated into organ donation behaviour. Statement of contribution What was already known? Demand for organs in the United Kingdom far outstrips supply, so finding strategies to increase registration on the organ donor register could save hundreds of lives per year. Despite the majority of people in the United Kingdom agreeing that organ donation is a good thing, most people do not register as donors. A limited amount of evidence of the impact of perceived reciprocity suggests that encouraging people to consider themselves as recipients and priming ideas of shared responsibility may increase the likelihood of their subsequent willingness to register. What does this study add? Novel evidence that employing a simple reciprocity prime increases organ donor registration intentions. Replication of findings across two separate studies. Novel examination of the impact of mode of delivery of messages to encourage organ donation. A basis for further research into the translation of intentions into organ donor registration behaviour.